Pengaruh Leader Humor Terhadap Job Crafting Dimediasi Oleh Perception Of Organizational Support Dan Work Engagement Pada Pegawai Sekretariat DPRD Provinsi Riau - Zanra, Sri Wahyuni (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
The purpose of this study was to determine the influence of Humor Leadership on Job Crafting mediated by Organizational Support and Work engagement of DPRD Secretariat Employees of Riau Province. The population in this study were all employees at the Riau Provincial DPRD Secretariat with a sample of 67 respondents. Data collection techniques using questionnaires and dissemination using Google Forms. The data analysis technique in this study was Structural Equation Modeling (SEM) using SmartPLS 3.0 as a data processing tool. The results of this study indicate that humorous leadership has a positive and significant effect on Perception Of Organizational Support, Work engagement and Job Crafting at the DPRD Riau Province Secretariat, Perception Of Organizational Support and Work engagement has a positive and significant effect on Job Crafting at the DPRD Riau Province Secretariat. The results of the study also show that Perception Of Organizational Support and Work engagement are able to mediate the relationship between leader humor and Job Crafting at the Secretariat of DPRD Riau Province.